In vis polemica con il mondo: Brucia la città di Giuseppe Culicchia come espressione di dialogo e scontro interculturale - Puto, Małgorzata (Romanica Silesiana)
Giuseppe Culicchia’s novel is an example of a literary polemic between the society and the individual who is, at least to a certain extent, a rebel. On the one hand, in Culicchia’s story, this might denote a person who stands up for their own personal opinions regardless of what anyone else says. On the other hand, however, a rebel may actually stand up against what is right, and may lose himself in drug and alcohol abuse. All in all, the novel focuses on being an individual and refusing to follow the crowd that forces you to think the same way they do even if it means becoming an outcast to the society. The novel is also a polemic, and polemics are not only a vehicle for the exchange of opinions, cultures, knowledge and ideas, but they also are the most significant sign of our times. Key words: Literary polemics, society vs. individual, rebel, culture.